(untitled) (Collection of scientific works «Modern structures of metal and wood», 2019)
The solar power of the world is growing at an exponential rate and so today is an effective solution to the introduction of solar power plants. The installation of alternative sources should start with energy audits, building and facility surveys, project documentation development. Installation of new technical equipment on the roof increases the load on the supporting structures. In this regard, the supporting elements of the building frame need reinforcement. The article presents the results of visual and instrumental examination of the grain composition located in the agricultural complex according to which deformations of the cover structures were revealed. A necessary element of the survey is to check the design of the structures, taking into account their actual condition. Verification calculation of structures, taking into account the effect of defects and damages, was carried out with the aim of: possibility of further operation without any restrictions; the need to strengthen the structures. The object of the study is the existing metal structures of the beam type - the farm, and the subject of the study are the methods of rational reinforcement and regulation of effort in such structures. Due to the increased load and insufficient cross-section of the farm elements, it is suggested to change the static scheme of the farm by installing additional elements of the grid - struts. The calculation of the farm is to determine the longitudinal efforts in all its rods, which will later be used in the selection (verification) of the cross-section of its elements. The study was performed using classical calculations of construction mechanics and methods of computer simulation experiment in the software complex "Lira CAD 2013", which is algorithmically based on the finite element method. The rational variant of strengthening of load-bearing structures is offered. The installation of solar panels on the roof of a building is possible provided that a working project is developed to strengthen the elements of the metal farm.